Establishing Control and Manufacturing Consent in Teachers’ Work - Rob George (New Zealand Journal of Teachers' Work)
Teaching is an individual act of one teacher in one classroom. It is also a collegial and collective endeavour. The job of teaching is a creative and complex activity; however, we may not often consider the underlying nature of this work. This article seeks to identify the structures of control and dynamics of consent and resistance at play in teachers’ work that results in the conversion of their labour potential into children’s learning. The focus of this exercise is generically teachers; however, a narrower reading would be a primary teacher with some classroom-based responsibility. Conclusions reveal that there are layers of structural and detailed control directing their labour, teachers consent stems from a range of sources and that resistance is present in a variety of ways, both visible set pieces and more oblique individual actions.